2004
DOI: 10.1538/expanim.53.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Di(2-ethylhexyl)phthalate on the Metabolism of Tryptophan to Niacin in Mice

Abstract: Abstract:We have reported the effect of di(2-ethylhexyl)phthalate (DEHP) on the tryptophan (Trp)-niacin pathway in rats. To clarify the universal effect of DEHP on rodents, we studied whether DEHP also has an effect on Trp metabolism in mice. Mice were fed a niacin-free, 20% casein diet supplemented with DEHP for 21 days. Feeding with DEHP decreased the body weight gain and increased the liver weight in correlation with the dose level of DEHP. The administration of DEHP significantly increased the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We found and have reported that mono(ethylhexyl)phthalate (MEHP), a metabolite of DEHP, inhibits the enzyme activity of ACMSD, and increases the formation of QA, causing it to increase further metabolites such as Nam. [7][8][9][10][11][12] Phthalic acid does not accumulate in the liver, so the reaction of QPRT might not be inhibited.…”
Section: Nadmentioning
confidence: 99%
See 1 more Smart Citation
“…We found and have reported that mono(ethylhexyl)phthalate (MEHP), a metabolite of DEHP, inhibits the enzyme activity of ACMSD, and increases the formation of QA, causing it to increase further metabolites such as Nam. [7][8][9][10][11][12] Phthalic acid does not accumulate in the liver, so the reaction of QPRT might not be inhibited.…”
Section: Nadmentioning
confidence: 99%
“…These esters have been detected in animals and humans. [2][3][4] We have reported that the administration of phthalic acid esters such as dibutylphtahlate 5,6) and DEHP [7][8][9][10][11][12] disturbed the metabolism of de novo NAD biosynthesis. Concretely, the administration of phthalic acid esters increased the formation of QA (a key intermediate of the de novo NAD biosynthesis) and its metabolites.…”
mentioning
confidence: 99%
“…2,3) These esters are widely distributed throughout the environment and have been detected in animals and humans. 4) We have already reported that the administration of phthalic acid the esters such as di-n-butylphthalate 5) and di(2-ethylhexyl)phthalate (DEHP) [6][7][8][9][10] disturbed the de novo nicotinamide (Nam) synthesis from tryptophan (Trp).…”
mentioning
confidence: 99%